A Viable University: Foresight, Logframe, Lifestyle and Risks - I. N. Zimin; V. M. Kartvelishvili (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The study continues the study of the fundamental characteristics of models of viable systems conducted by the authors. The current issues of construction, reorganization and preservation of the life-incapable structure of a higher educational institution - university U, representing a recursive active subsystem of the educational environment, which is part of the universe-society, are considered. The formalized definitions of an absolutely viable, viable, conditionally viable and non-viable system are given, allowing from a mathematical point of view to assess the optimality of the structure and the efficiency of the system functioning. The analysis of the structure and functioning of a viable university is implemented in the conceptual framework of foresight design based on logframe technologies, which makes it possible to create a system that meets the strategic goals of the universe and the tactical settings of the educational environment. In the process of describing logframe methods based on the foresight approach, real risk situations arising in the modern education system, the university environment and higher educational institutions due to economic, social, managerial and psychological factors of the impact of external and internal environments of recursive active systems are significantly taken into account. The presented conceptual schemes allow us to take into account not only the structural features of the educational organization, but also the psychosocial situation in the team, which determines the stimulating and motivational aspects of personnel management. Examples of higher educational institutions are given, whose structures and training procedures have effectively met and continue to meet the needs and goals of the universe for several successive technological structures, remaining advanced educational and scientific-educational systems of the world level. A brief overview of research and practices in the presented field of knowledge is given, based on the approaches and methods of teaching, scientific and teaching experience of the authors. The presented material is useful for the process of formalization of conceptual aspects of the theory of viable systems, classification of risk situations in the educational process, adaptation of foresight and logframe technologies to the practice of diagnosing and designing effective educational structures that meet the modern socio-economic requirements of technological structures of developed societies.